2005
DOI: 10.1021/bm049271i
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Novel Folic Acid-Functionalized Biocompatible Block Copolymers by Atom Transfer Radical Polymerization for Gene Delivery and Encapsulation of Hydrophobic Drugs

Abstract: Two synthetic routes to folic acid (FA)-functionalized diblock copolymers based on 2-(methacryloyloxy)ethyl phosphorylcholine [MPC] and either 2-(dimethylamino)ethyl methacrylate [DMA] or 2-(diisopropylamino)ethyl methacrylate [DPA] were explored. The most successful route involved atom transfer radical polymerization (ATRP) of MPC followed by the tertiary amine methacrylate using a 9-fluorenylmethyl chloroformate (Fmoc)-protected ATRP initiator. Deprotection of the Fmoc groups produced terminal primary amine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
119
0

Year Published

2008
2008
2013
2013

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 151 publications
(121 citation statements)
references
References 21 publications
2
119
0
Order By: Relevance
“…[16,17] Briefly, MPC was polymerized first in a 3:2 methanol/isopropyl alcohol solvent mixture using [MPC]:[Fmoc-protected initiator]:[CuBr]:[bpy] ¼ 30:1:1:2 under a nitrogen atmosphere for approximately 2 h at 20 8C. The required amount of the DPA monomer was then added to this reaction solution and 1 H NMR spectroscopy was used to monitor the reaction until monomer consumption was complete.…”
Section: Synthesis Of Pmpc-pdpa Diblock Copolymersmentioning
confidence: 99%
See 1 more Smart Citation
“…[16,17] Briefly, MPC was polymerized first in a 3:2 methanol/isopropyl alcohol solvent mixture using [MPC]:[Fmoc-protected initiator]:[CuBr]:[bpy] ¼ 30:1:1:2 under a nitrogen atmosphere for approximately 2 h at 20 8C. The required amount of the DPA monomer was then added to this reaction solution and 1 H NMR spectroscopy was used to monitor the reaction until monomer consumption was complete.…”
Section: Synthesis Of Pmpc-pdpa Diblock Copolymersmentioning
confidence: 99%
“…The resulting purified Fmoc-MPC-DPA diblock copolymers were treated with DBU in methanol to obtain the resulting primary amine-functionalized copolymer (H 2 N-MPC-DPA) and purified as previously reported. [16,17] Conjugation of Folic Acid to MPC-DPA Diblock Copolymers Folic acid was conjugated to H 2 N-MPC-DPA using the protocol described previously. [17] Folate conjugation reaction was carried out in a 3:2 water/dimethyl sulfoxide (DMSO) mixture containing folic acid in the presence of EDC.HCl and NHS as condensing agents.…”
Section: Synthesis Of Pmpc-pdpa Diblock Copolymersmentioning
confidence: 99%
“…Nevertheless, the characteristic proton resonance peak of FA located at 8.66 ppm is separated from those of the conjugated backbone. [ 31 ] Thereby, the molar percentage of FA in P4 is calculated to be ∼ 60%.…”
Section: Synthesis and Characterizationmentioning
confidence: 99%
“…[1][2][3][4] Some synthetic routes have been exploited to synthesize amphiphilic block copolymers, including living anionic polymerization, 5-7 cationic polymerization, [8][9][10] and the controlled/ ''living'' radical polymerization and so forth. [11][12][13] Among these methods reported, living radical polymerization (LRP), which exemplifies stable free radical polymerization (SFRP), 14,15 atom transfer radical polymerization (ATRP), [16][17][18] and reversible addition-fragmentation transfer polymerization (RAFT), [19][20][21] has become preferred to others lying in its accurate control of molecular weight, polydispersity, and chain-end functionality. The combination of fundamentally different synthetic techniques, however, proved to be more suitable to the synthesis of block copolymers, which has motivated more researchers to synthesize various block copolymers by this strategy.…”
Section: Introductionmentioning
confidence: 99%
“…As known to date, ATRP has been successfully employed to the synthesis of many macromolecules with predetermined architectures. [16][17][18] Chemoenzymatic method, which combines eROP with ATRP, provides a new strategy to synthesize amphiphilic block copolymers with controlled molecular weight, well-tailored architecture and precisely adjustable functionality owing to its integration of advantages of both polymerization techniques. 36,37 Since Andreas Heise et al first reported the chemoenzymatic synthesis of AB-type diblock copolymer PCL-b-PSt via the combination of eROP of CL and ATRP of St, 38 more researchers have attempted to employ chemoenzyme-catalyzed routes to construct block copolymers.…”
Section: Introductionmentioning
confidence: 99%